2018
DOI: 10.1371/journal.pone.0190737
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic determinants of physical activity across the life course: A "DEterminants of DIet and Physical ACtivity" (DEDIPAC) umbrella literature review

Abstract: BackgroundTo date, the scientific literature on socioeconomic correlates and determinants of physical activity behaviours has been dispersed throughout a number of systematic reviews, often focusing on one factor (e.g. education or parental income) in one specific age group (e.g. pre-school children or adults). The aim of this umbrella review is to provide a comprehensive and systematic overview of the scientific literature from previously conducted research by summarising and synthesising the importance and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
177
7
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(204 citation statements)
references
References 38 publications
17
177
7
3
Order By: Relevance
“…We found no differences in leisure-time physical activity between the occupational categories, which is contrary to some previous studies which have used self-reported physical activity as an outcome 2. Nevertheless, our results are similar to several studies using objective measures for physical activity which have not observed differences in leisure-time physical activity between manual and non-manual occupations 5–8.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…We found no differences in leisure-time physical activity between the occupational categories, which is contrary to some previous studies which have used self-reported physical activity as an outcome 2. Nevertheless, our results are similar to several studies using objective measures for physical activity which have not observed differences in leisure-time physical activity between manual and non-manual occupations 5–8.…”
Section: Discussioncontrasting
confidence: 85%
“…Generally, non-manual occupational status has been found to associate with more total or leisure time physical activity, but with less occupational physical activity 2. However, the research on physical activity across different occupations has mostly relied on self-reported measures of physical activity,1 which usually capture only moderate-to-vigorous physical activity (MVPA) and are prone to reporting bias 3.…”
Section: Introductionmentioning
confidence: 99%
“…Recent literature from LMICs has begun to explore how the school environment is an important modifier of food and physical activity choices for adolescent girls, similar to well-established findings from HICs. 5,6,15,16 However, most of this work has been conducted in large metropolitan settings (including in Guatemala) and much less is known about the choices of adolescent girls from outside these areas. 18,20 In addition, comparative work on the choices of out-of-school girls has not been conducted, despite the importance of this issue in LMICs, where many adolescents are not enrolled in school due to multiple reasons, including work and pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…There is an extensive literature on the social and environmental factors that impact adolescents' decision making around diet and activity. [2][3][4][5][6][7][8][9] In particular, the school environment has been well studied, both as a formative environment shaping diet and activity behaviors and, consequently, a potential site for interventions a These authors contributed equally. designed to promote healthy behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Apple Watch or Garmin's) can potentially provide such information if the data is further processed [8]. However, access to such devices is challenging at a population level, particularly amongst the least active who also tend to be amongst the least affluent parts of society [18]. Therefore, the Active 10 intervention started with the development of a custom selfmonitoring app, especially designed to track the achievement of daily bouts of 10 minutes of brisk walking via mobile phone.…”
Section: Designing Active 10mentioning
confidence: 99%